Transitioning from Stiff Chest Tubes to Soft Pleural Catheters: Prospective Assessment of a Practice Change - Martin, Kathryn; Emil, Sherif; Zavalkoff, Samara; Lo, Andrea; Ganey, Michael; Baird, Robert; Gaudreault, Josee; Mandel, Romain; Perreault, Thérèse; Pharand, Andréane (European Journal of Pediatric Surgery, 2013)
Background Tube thoracostomies in children are required for multiple indications and can be associated with significant discomfort. In 2010, a multidisciplinary team at our institution developed a protocol to replace stiff chest tubes with 8.5-French soft pleural catheters in children requiring pleural drainage.Methods Before initiating the protocol, an audit sheet was developed to prospectively capture data regarding insertion, removal, complications, and success. After 8 months of new protocol utilization, these data were reviewed, along with a retrospective review of the patients' charts.Results Twenty-three patients had 33 pleural catheters inserted over an 8-month period. Mean age was 6.7 years (1 day to 17 years). Indications for insertion were pneumothorax (24%), simple effusion (24%), chylothorax (27%), parapneumonic effusion/empyema (21%), and malignant effusion (3%). Complications included premature dislodgment (33%), blockage (15%), pneumothorax (3%), and bleeding (3%). Mean duration of pleural drainage was 7.27 days (0 to 37 days). Pleural drainage was successful in 91% of patients.Conclusion Soft pleural catheters are an acceptable alternative to traditional stiff chest tubes in the pediatric population. Premature dislodgment was the most common problem. Prospective audits are extremely valuable in assessing new procedural protocols and practice changes.
Keywords: pleural; drainage; effusion; catheter; pneumothorax